Mixed ductal-acinar cell carcinoma of the pancreas: A case report - Shigaki, Takahiro (Mol Clin Oncol, 2019)
Mixed carcinoma of the pancreas is defined as the concurrent existence of pancreatic ductal carcinoma, acinar cell carcinoma, and/or islet cell carcinoma within the same neoplasm. We herein report a rare case of mixed ductal-acinar cell carcinoma in a 74-year-old man who was undergoing treatment for hypertension and diabetes at another hospital. After an abrupt worsening of his blood glucose control, the patient was referred to our hospital for further evaluation. Abdominal contrast-enhanced computed tomography and magnetic resonance imaging revealed a tumor with a multilocular cystic lesion in the head of the pancreas. Endoscopic retrograde cholangiopancreatography revealed obstruction of the main pancreatic duct and dilation of the dorsal pancreatic duct; in addition, adenocarcinoma was detected in the pancreatic juice cytology. Based on the abovementioned findings, the patient was diagnosed with carcinoma of the pancreatic head and underwent subtotal stomach-preserving pancreaticoduodenectomy. Based on the histopathological and immunohistochemical findings, the patient was diagnosed with mixed ductal-acinar cell carcinoma. The patient was prescribed TS-1 as postoperative adjuvant chemotherapy upon discharge. However, treatment was discontinued 2 months later due to marked general malaise, and the patient succumbed to tumor recurrence in the residual pancreas 12 months after the surgery.